1973
DOI: 10.1002/dev.420060209
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of the onset of drinking and plasma osmotic pressure regulation

Abstract: Pertinent behavioral and physiological variables related to the development of the onset of drinking were measured in albino rats of both sexes between 14 and 100 days of age. Under ad libitum conditions all variables studied were found to increase as a function of age. Following a subcutaneous 16% NaCl injection mean latency to drink was found to range from 4.6-9.5 min across ages. Plasma osmolality levels at the initiation of drinking were found to increase as a function of age and were found to be elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 10 publications
4
20
1
Order By: Relevance
“…These results are in agreement with Jelinek (1961) and Almli (1973) in that ad libitum plasma osmolality was observed to increase with age. This may be an example of what Adolph (1968) has referred to as a set point change with development either (Wright et al, in press).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These results are in agreement with Jelinek (1961) and Almli (1973) in that ad libitum plasma osmolality was observed to increase with age. This may be an example of what Adolph (1968) has referred to as a set point change with development either (Wright et al, in press).…”
Section: Discussionsupporting
confidence: 95%
“…Further, because our main concern was with percent elevation in plasma osmolality at drinking initiation and not with absolute levels we felt justified in using the heart puncture technique. With a set volume of heparin of 15-20 p1 in each syringe, we obtained ad llbitum plasma osmolality concentrations in mature and in young rats that agree with the absolute levels reported elsewhere (Almli, 1973;Friedman & Campbell, 1974;Hatton & Almli, 1969;Kutscher, 1971).…”
Section: Subjects and Proceduresmentioning
confidence: 72%
See 1 more Smart Citation
“…Rat pups as young as 2 days old respond to cellular dehydration with a vigorous increase in mouthing and swallowing when water is infused directly into their mouths (Almi, 1973;Bruno, 1981;Wirth & Epstein, 1976). This demonstrates the precocial development of a physiological sensitivity to dehydration, and the capability of young pups to increase oromotor responding when water contacts the mouth.…”
Section: Introductionmentioning
confidence: 93%
“…These results suggest that, although intake is enhanced by both cellular and extracellular dehydration in very young pups, the behavioral changes responsible for the enhancement of intake after cellular dehydration are different from the behavioral changes resulting from extracellular dehydration. This dissociation of behavioral effects of dehydration in young pups demonstrates that intake measures alone may obscure subtle differences in behavior and argues for the utility of dissection of behavioral components in understand- Numerous studies have demonstrated a profound impact of hydrational state on ingestion in rat pups from very early ages (e.g., Adolph, 1957;Almli, 1973; …”
mentioning
confidence: 98%